Description of a new species of Kibakoganea from Vietnam (Coleoptera: Scarabaeidae: Rutelinae: Rutelini) - Do, Cuong (Zootaxa, 2013)
Kibakoganea canhcamsung new species (holotype male and paratype female), from Quang Nam province, Vietnam, is described and illustrated based on two specimens. The genus Kikobaganea Nagai was erected as subgenus of Fruhstoferia (Nagai 1984). Hirasawa (1992) later elevated Kibakoganea to the generic level. In that paper, Hirasawa erected two new related genera from Malaysia, Muramotokoganea Hirasawa and Nagainokoganea Hirasawa. The latter genus was originally defined based on two species N. malayanus from Malaysia and N. curta from Laos. Later, N. curta was moved to the genus Pukupuku Muramoto with P. kasurai, another species from Vietnam, based on similarities in the male genitalia (Muramoto 2006). Therefore, the genus Nagainokoganea only contains the type species N. malayanus, and perhaps the classification should be reconsidered or redefined with updated characteristics. The similarities of N. malayanus with Didrepanephorus bifurcifer Wood Mason suggest the possibility that Nagainokoganea should be a synonym or subgenus of Didrepanephorus Wood Mason.